A Review of Behaviorist Learning Theory and its Impact on the Learning Process in Schools - Alfajri Yusra; Neviyarni S; Erianjoni Erianjoni (Postgraduate School, Universitas Negeri Padang, 2022)
Behavioristic learning theory and its influence on learning and the learning process are discussed in this article. According to behavioristic theory, learning results in behavior modification. Behavioristic learning theories are hypotheses about how people learn, and they argue that rewards and reinforcement play a role in learning. According to this belief, the behavior will stop if it receives punishment. The expression